INFLUENCE OF ETHYLMETHYLHYDROXYPYRIDINE SUCCINATE INCLUSION IN ANTIHYPERTENSIVE THERAPY ON THE CONDITION OF THE ARTERIAL WALL IN YOUNG PATIENTS WITH HYPERTENSION - Bilovol, O.M.; Kniazkova, I.I.; Mishchenko, V.M.; Kuzminova, N.V.; Starenkyi, V.P.; Zhadan, A.V.; Bogun, M.V. (World of Medicine and Biology, 2023)
The purpose of the study was to evaluate the impact of combined antihypertensive therapy including ethylmethylhydroxypyridine succinate on blood pressure levels, arterial stiffness and quality of life in young patients with hypertension. A total of 60 patients (mean age, 41.7±1.3 years) with grade 2 hypertension who were not taking regular antihypertensive therapy were examined. After baseline data collection, 30 patients (group 1) were administered basic therapy with antihypertensive drugs and ethylmethylhydroxypyridine succinate, and 30 patients (group 2) were administered basic therapy, which included a combination of lisinopril 10–20 mg/day and amlodipine 5–10 mg/day for 8 weeks. After the treatment, a decrease in systolic and diastolic blood pressure levels in groups 1 and 2 by 23.3 mm Hg and 17.5 mm Hg and 14.3 mm Hg and 8.4 mm Hg, respectively, was observed (all p
Keywords: hypertension; young age; combined antihypertensive therapy; ethylmethylhydroxypyridine succinate; arterial stiffness; quality of life